ANALISIS PRODUKTIVITAS, PENDAPATAN DAN KESEJAHTERAAN PETANI KARET EKS UPP TCSDP KUALU DI DESA ALAM PANJANG KECAMATAN RUMBIO JAYA KABUPATEN KAMPAR - Febronika, Roza; Rifai, Ahmad; Yusri, Jumatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This study aims to analyze the productivity, to analyze the revenue, to analyze of the households income structure, to analyze the pattern of households expenditure, and to analyze the welfare of households of the smallholder rubber plantation of ex-TCSDP development. Research was done by survey at Alam Pajang Village. Data were collected from 16 small-holders rubber farmers using purposive sampling and census technique. Analysis of the results showed that the productivity of smallholder rubber plantation as 2.56 ton/ha/year, the revenues of samallholder rubber plantation as Rp. 17,679,095.84/ha/year. The structure of household income derived from agriculture is 57.42 percent and 42.58 percent for non-agricultural income. The pattern of household expenditure shown that the food expenditure as 41.89 percent and non-food expenditures as 58.11 percent. Result also show that the household of the smallholder rubber plantation at Alam Panjang Village have the total expenditure more than 240 kg of rice equivalent. The household of small-holders rubber plantation have the total expenditure above the poverty line (Rp. 336.681/capita/month). The household welfare using the 14 indicators of relative poverty by Indonesian Statistic show that 68.75 percent household have ability to fullfill the basic need or prosperous, while 31.25 percent is almost prosperous. Key words : Rubber Farmer, Productivity, Income, Outcome, Welfare